A NEW APPROACH FOR FINDING AN INITIAL SOLUTION NEAR TO OPTIMUM FOR THE SOLID TRANSPORTATION PROBLEMS - Abdelati, Mohamed; Abd-El-Tawwab, Ali M.; Elsayed Elsayed M. Ellimony; Rabie, Mohamed (AGPE THE ROYAL GONDWANA RESEARCH JOURNAL OF HISTORY, SCIENCE, ECONOMIC, POLITICAL AND SOCIAL SCIENCE, 2023)
The solid transportation problem (STP) is a particular type of linear programming problem. This paper presented an approach for solving STP in a highly efficient and a few iterations until finding an optimal solution. The proposed method provides an initial solution near to optimum solution to the solid transportation problem close to the optimal solution. Using Lingo software, a numerical example was used to compare the solution from the proposed method to the optimal solution.